2023
DOI: 10.1371/journal.pgph.0001597
|View full text |Cite
|
Sign up to set email alerts
|

Facebook addiction and its related factors among medical students; a cross- sectional study in Bangladesh

Abstract: There is mounting evidence that Facebook Addiction is associated with poor mental health, physical symptoms, social dysfunction, and despair among the adolescent and youth population. The current study set out to identify the prevalence of Facebook Addiction among Bangladeshi medical students as well as its influencing factors. This cross-sectional survey was conducted on 720 randomly selected medical students from eight public medical colleges from January to June 2022. Data were obtained using a semi- struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…University students reported Facebook addiction problems in 57 (16.2 %) cases. These findings are consistent with a study conducted on Bangladeshi university students after the COVID-19 pandemic, which reported a prevalence of Facebook addiction at 29.4 % [ 45 ]. Another study on Trinidadian university students reported that 8.5 % presented a high risk of Facebook addiction [ 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…University students reported Facebook addiction problems in 57 (16.2 %) cases. These findings are consistent with a study conducted on Bangladeshi university students after the COVID-19 pandemic, which reported a prevalence of Facebook addiction at 29.4 % [ 45 ]. Another study on Trinidadian university students reported that 8.5 % presented a high risk of Facebook addiction [ 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…Most of the studies have collectively suggested that spending a significant amount of time on these social media platforms can have a damaging effect on psychological well-being and can also increasing the risk of experiencing psychological stress, depression, and anxiety due to various reasons. Kross et al (2013), Balakrishnan and Shamim (2013), Beardsmore (2015) and Karim et al (2023) reported the effect of facbook, WhatsApp and Instagram usage on the psychological stress. Similarly, Gupta et al (2022), Al-Naami et al (2023) and Pirnes et al (2023) suggested that increased time spent on social media platforms was associated with neck pain.…”
Section: Development Of the Path Analysis Modelmentioning
confidence: 99%
“…Throughout the world, the study of medicine is seen as being intrinsically difficult and demanding 21 due to the pressures of the classroom, overexpectations, 13 the demands of the workplace, burn-out and depression (particularly among younger doctors), as well as the ongoing trouble of balancing job, family and financial obligations. 7 In addition, other factors that contribute to suicidal behaviour among medical students include chronic stress, 22 poor mental health status, 15 academic stress, familial pressure, depression, 10 relationship status, drug addiction, alcohol use, 12 online addictions, 23 sleeping difficulties, thoughts of dropping out, physical or sexual assault, 1 parenting style 24 and family history. 10 11 …”
Section: Introductionmentioning
confidence: 99%